Aqueous lithium ion battery taking manganese dioxide as negative electrode material and preparation method of aqueous lithium ion battery
By using manganese dioxide as the negative electrode material and high specific capacity positive electrode material in aqueous lithium-ion batteries, combined with appropriate aqueous electrolyte and additives, the limitations of the negative electrode material stability and electrochemical performance of traditional aqueous lithium-ion batteries are solved, and the limitations of the negative electrode material of traditional aqueous lithium-ion batteries are achieved. Higher stability, safety and energy density.
Patent Information
- Application Number
- CN202411630878.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-02-14
AI Technical Summary
The use of graphite materials in traditional water system lithium-ion batteries has limitations in the use of negative electrode materials, which limits the performance and life of the battery.
Manganese dioxide (MnO2) is used as the negative electrode material, combined with LiCoO2, LiMn2O4, LiFePO4 or LiNi0.5Mn1.5O4 as the positive electrode material, and appropriate additives are added to the aqueous electrolyte to improve the overall stability of the battery.
It improves the stability and safety of water-based lithium-ion batteries, enhances the energy density and cycle stability of the battery, reduces manufacturing costs, and extends the service life of the battery.
Smart Images

Figure CN119447513A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to an aqueous lithium ion battery using manganese oxide as a negative electrode material and an application thereof. Background Art
[0002] With the transformation of the global energy structure and the rapid development of electric vehicles, portable electronic devices and other fields, the demand for high-performance and environmentally friendly battery technology is increasing. Traditional lithium-ion batteries use organic electrolytes. Although they have high energy density, they have safety hazards such as flammability and explosion. In addition, the production and recycling of organic electrolytes also impose a burden on the environment. Aqueous lithium-ion batteries have become a research hotspot in the field of battery technology because they use aqueous electrolytes, have the advantages of high safety, non-flammability and non-explosion, environmental friendliness and low cost. However, the selection of electrode materials for aqueous lithium-ion batteries and the improvement of electrochemical performance are the main technical challenges that restrict their widespread application. In terms of negative electrode materials, traditional graphite materials have limitations in stability and electrochemical performance in aqueous electrolytes, which limits the performance and life of aqueous lithium-ion batteries. Therefore, the development of new and high-performance negative electrode materials is crucial to promote the commercial application of aqueous lithium-ion batteries.
[0003] Manganese dioxide (MnO2) is a material with a high theoretical specific capacity. It is inexpensive, environmentally friendly, and has excellent safety performance, reducing the risk of battery safety accidents. In addition, MnO2 has a higher discharge platform, and the battery voltage matched with the positive electrode is lower, within the decomposition voltage of the aqueous electrolyte, which improves the overall stability of the battery. In addition, its preparation process is mature, easy to mass produce and modify, making it a negative electrode material with both performance and application potential in aqueous lithium-ion batteries. Summary of the invention
[0004] The present invention provides an aqueous lithium-ion battery using manganese dioxide as a negative electrode material and a preparation method thereof. The objective of the present invention is to provide a new type of negative electrode material with excellent performance for aqueous lithium-ion batteries, improve the stability of aqueous lithium-ion batteries, and promote technological progress and application development in this field.
[0005] The purpose of the present invention is to adopt the following technical solutions to achieve:
[0006] An aqueous lithium-ion battery, the battery comprising: a battery housing and a positive electrode, a negative electrode, an aqueous electrolyte and a diaphragm placed in the battery housing; the active material of the positive electrode comprises LiCoO2, LiMn2O4, LiFePO4 or LiNi 0.5 Mn 1.5O4, the selected material has high specific capacity and good cycle stability; the active material of the negative electrode includes one or more materials of α-MnO2, γ-MnO2, δ-MnO2, these materials have a higher discharge platform, and the battery voltage matched with the positive electrode is lower, within the decomposition voltage of the aqueous electrolyte, which improves the overall stability of the battery.
[0007] In the above aqueous electrolyte, the molar concentration of lithium salt dissolved in the mixed solvent can be 0.05 to 20 mol / kg; the molar mass ratio of water to additives is 0.1:2 to 3:1.
[0008] Preferably, the aqueous electrolyte comprises a water-soluble lithium salt solution, and the lithium salt comprises at least one of lithium perchlorate (LiCIO4), lithium nitrate (LiNO3), lithium sulfate (LiSO4), lithium hexafluorophosphate (LiPF6), lithium bis(oxalate borate) (LiB(C2O4)2), lithium difluorooxalatoborate (LiBF4) and lithium bis(trifluoromethylsulfonyl imide) (LiTFSI);
[0009] Preferably, the additive is selected from at least one of carbonate compounds, sulfonyl compounds and cyano compounds. Carbonate compounds include ethylene carbonate and fluoroethylene carbonate; sulfonyl compounds include dimethyl sulfoxide, thionyl chloride, sulfuryl chloride and benzenesulfonyl chloride; cyano compounds include acetonitrile, succinonitrile and glutaronitrile.
[0010] Preferably, the diaphragm comprises a polyethylene diaphragm, a polypropylene diaphragm, a polypropylene-polyethylene composite diaphragm, a glass fiber diaphragm, a non-woven fabric or a Nafion membrane.
[0011] Based on the same inventive concept, the present invention also provides a method for preparing an aqueous lithium-ion battery, which is used to prepare the aqueous lithium-ion battery, and the method comprises the following steps:
[0012] Will contain LiCoO2, LiMn2O4, LiFePO4 or LiNi 0.5 Mn 1.5 A positive electrode slurry containing α-MnO2, γ-MnO2, and δ-MnO2 is coated on the surface of the positive electrode collector and heated and dried to form a positive electrode; a negative electrode slurry containing one or more of α-MnO2, γ-MnO2, and δ-MnO2 is coated on the surface of the negative electrode collector and heated and dried to form a negative electrode; the positive electrode, separator, and negative electrode are processed and formed into the battery casing, and an aqueous electrolyte is added to the battery casing and then sealed to obtain the aqueous lithium-ion battery.
[0013] Preferably, the said will contain LiCoO2, LiMn2O4, LiFePO4 or LiNi 0.5 Mn 1.5The positive electrode slurry of O4 is coated on the surface of the positive electrode collector to prepare the positive electrode sheet, which includes: grinding and mixing the positive electrode material, conductive carbon black (Super P), and polyvinylidene fluoride (PVDF) in a mass ratio of 6-9:0.2-4:0.2-4, and then adding N-methylpyrrolidone (NMP) and mixing evenly to obtain the positive electrode slurry.
[0014] Preferably, the positive electrode current collector includes copper foil, stainless steel foil, aluminum foil, titanium foil, graphite foil, nickel foil, carbon fiber cloth or a composite current collector, such as conductive resin, carbon-coated aluminum foil and titanium-nickel shape memory alloy.
[0015] Preferably, the process of coating a negative electrode slurry comprising one or more materials of α-MnO2, γ-MnO2, and δ-MnO2 on the surface of a negative electrode current collector to form a negative electrode comprises: grinding and mixing the negative electrode material with conductive carbon black (Super P) and polyvinylidene fluoride (PVDF) in a mass ratio of 6-9:0.2-4:0.2-4, and then adding N-methylpyrrolidone (NMP) and mixing evenly to obtain the negative electrode slurry.
[0016] Preferably, the negative electrode current collector includes copper foil, stainless steel foil, aluminum foil, titanium foil, graphite foil, nickel foil, carbon fiber cloth or a composite current collector, such as conductive resin, carbon-coated aluminum foil and titanium-nickel shape memory alloy.
[0017] Preferably, the temperature of the heating and drying is 50-200°C.
[0018] Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects:
[0019] (1) The aqueous lithium-ion battery disclosed in the present invention uses a highly safe water-soluble lithium salt and an additive as an electrolyte, thereby improving the stability and safety of the battery;
[0020] (2) The present invention uses manganese dioxide (MnO2) as the negative electrode material, which has a high theoretical specific capacity and stable electrochemical performance, which helps to improve the energy density and cycle stability of the battery.
[0021] (3) The present invention uses LiCoO2, LiMn2O4, LiFePO4 or LiNi 0.5 Mn 1.5 O4 is used as the positive electrode, and one or more materials among α-MnO2, δ-MnO2, γ-MnO2 are used as the negative electrode. The manufacturing process of the selected negative electrode material is mature, easy to mass produce and modify, which reduces the manufacturing cost of lithium batteries;
[0022] (4) The present invention adds additives to the electrolyte to inhibit the decomposition of water and expand the electrochemical window of water decomposition in the system, thereby improving the performance and service life of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is the constant current charge and discharge curve of the α-MnO2 negative electrode material in Example 1.
[0024] Figure 2 This is the constant current charge and discharge curve of the γ-MnO2 negative electrode material in Example 2.
[0025] Figure 3 This is the constant current charge and discharge curve of the δ-MnO2 negative electrode material in Example 3. DETAILED DESCRIPTION
[0026] Example 1: Preparation of α-MnO2 negative electrode material and battery assembly
[0027] (1) Preparation of negative electrode material: 70% α-MnO2 and 20% superconducting carbon black (Super P) were ground and stirred uniformly, and then 10% polyvinylidene fluoride (PVDF) binder was added to grind into slurry. Then, N-methylpyrrolidone (NMP) was added to the mixture as a solvent to obtain a viscous slurry. The slurry was evenly coated on the graphite foil current collector, the coating thickness was controlled to be 150 μm, and dried at 60°C for 6 hours to remove the NMP solvent.
[0028] (2) Preparation of positive electrode materials: Commercially available LiCoO2 was used as the positive electrode material, mixed with 10% conductive carbon black and 10% PVDF, coated on aluminum foil, and subjected to the same drying process.
[0029] (3) Battery assembly: The positive electrode, separator, and negative electrode are stacked in sequence and loaded into a CR2032 coin-type battery case. A 2 M lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) aqueous solution is injected as the electrolyte. Glass fiber is used as the separator. Finally, the battery case is sealed.
[0030] (4) Performance test: The battery was subjected to constant current charge and discharge test at a current density of 0.2 mA / g, with a test voltage range of 0 to 1.8 V, and a cycle stability test of 500 cycles, recording the charge and discharge capacity and voltage platform of each cycle. After testing, the assembled battery showed high capacity but poor stability. Figure 1 The constant current charge and discharge curve of α-MnO2 negative electrode material is shown. The initial specific capacity of α-MnO2 is 192mAh / g, which is relatively high.
[0031] Example 2: Preparation of γ-MnO2 negative electrode material and battery assembly
[0032] (1) Preparation of negative electrode material: Using the same method as in Example 1, 70% γ-MnO2 and 20% superconducting carbon black (Super P) were ground and stirred uniformly, and then 10% polyvinylidene fluoride (PVDF) binder was added to grind into slurry. Then, N-methylpyrrolidone (NMP) was added to the mixture as a solvent to obtain a viscous slurry. The slurry was evenly coated on the graphite foil current collector with a coating thickness of 150 μm and dried at 60°C for 6 hours to remove the NMP solvent.
[0033] (2) Preparation of positive electrode materials: Commercially available LiCoO2 was used as the positive electrode material, mixed with 10% conductive carbon black and 10% PVDF, coated on aluminum foil, and subjected to the same drying process.
[0034] (3) Battery assembly: The positive electrode, separator, and negative electrode are stacked in sequence and loaded into a CR2032 coin-type battery case. A 2 M lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) aqueous solution is injected as the electrolyte. Glass fiber is used as the separator. Finally, the battery case is sealed.
[0035] (4) Performance test: The battery was subjected to constant current charge and discharge test at a current density of 0.2 mA / g with a test voltage range of 0 to 1.8 V. A cycle stability test was performed for 500 cycles, and the charge and discharge capacity and voltage platform of each cycle were recorded. Figure 2 The constant current charge and discharge curve of the battery composed of γ-MnO2. The initial specific capacity of γ-MnO2 is 94 mAh / g, which is lower than the initial specific capacity of α-MnO2.
[0036] Example 3: Preparation of δ-MnO2 negative electrode material and battery assembly
[0037] (1) Preparation of negative electrode material: Using the same method as in Example 1, 70% δ-MnO2 and 20% superconducting carbon black (Super P) were ground and stirred evenly, and then 10% polyvinylidene fluoride (PVDF) binder was added to grind into slurry. Then, N-methylpyrrolidone (NMP) was added to the mixture as a solvent to obtain a viscous slurry. The slurry was evenly coated on the carbon fiber cloth current collector with a coating thickness of 150 μm, and dried at 60°C for 6 hours to remove the NMP solvent.
[0038] (2) Preparation of positive electrode materials: Commercially available LiCoO2 was used as the positive electrode material, mixed with 10% conductive carbon black and 10% PVDF, coated on aluminum foil, and subjected to the same drying process.
[0039] (3) Battery assembly: The positive electrode, separator, and negative electrode are stacked in sequence and loaded into a CR2032 coin-type battery case. A 2 M lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) aqueous solution is injected as the electrolyte. Glass fiber is used as the separator. Finally, the battery case is sealed.
[0040] (4) Performance test: The battery was subjected to constant current charge and discharge test at a current density of 0.2 mA / g with a test voltage range of 0 to 1.8 V. A cycle stability test was performed for 500 cycles, and the charge and discharge capacity and voltage platform of each cycle were recorded. Figure 3 The constant current charge and discharge curve of the battery composed of δ-MnO2. The initial specific capacity of δ-MnO2 is 126 mAh / g, which is higher than that of γ-MnO2.
[0041] Example 4: Preparation of α-MnO2, γ-MnO2, δ-MnO2 mixed negative electrode material and battery assembly
[0042] (1) Preparation of negative electrode materials: α-MnO2, γ-MnO2, and δ-MnO2 were mixed in a ratio of 1:1:1, with a mass ratio of 60% and 30% superconducting carbon black (Super P). After grinding and stirring, 10% polyvinylidene fluoride (PVDF) binder was added to grind into slurry. Then, N-methylpyrrolidone (NMP) was added to the mixture as a solvent to obtain a viscous slurry. The slurry was evenly coated on a graphite foil current collector with a coating thickness of 200 μm, and dried at 60°C for 8 hours to remove the NMP solvent.
[0043] (2) Preparation of positive electrode material: Commercially available LiMn2O4 was used as the positive electrode material, mixed with 10% conductive carbon black and 10% PVDF, coated on aluminum foil, and subjected to the same drying process.
[0044] (3) Battery assembly: The positive electrode, separator and negative electrode are stacked in sequence and placed in a CR2032 coin-type battery case. A 2M lithium nitrate (LiNO3) aqueous solution is injected as the electrolyte. A polypropylene separator is used and the battery case is finally sealed.
[0045] (4) Performance test: The battery was subjected to constant current charge and discharge test at a current density of 2 mA / g, with a test voltage range of 0 to 1.8 V, and a cycle stability test for 500 cycles.
[0046] Example 5: Preparation of δ-MnO2 negative electrode material and battery assembly
[0047] (1) Preparation of negative electrode material: Using the same method as in Example 1, 80% δ-MnO2 and 10% superconducting carbon black (Super P) were ground and stirred evenly, and then 10% polyvinylidene fluoride (PVDF) binder was added to grind into slurry. Then, N-methylpyrrolidone (NMP) was added to the mixture as a solvent to obtain a viscous slurry. The slurry was evenly coated on a graphite foil current collector with a coating thickness of 200 μm and dried at 60°C for 6 hours to remove the NMP solvent.
[0048] (2) Preparation of positive electrode materials: Commercially available LiCoO2 was used as the positive electrode material, mixed with 10% conductive carbon black and 10% PVDF, coated on aluminum foil, and subjected to the same drying process.
[0049] (3) Battery assembly: The positive electrode, separator and negative electrode are stacked in sequence and loaded into a CR2032 coin-type battery case. A 2M electrolyte solution with a molar ratio of water to additive dimethyl sulfoxide of 1:0.5 is injected, and the electrolyte is 2M LiNO3. Glass fiber is used as a separator, and finally the battery case is sealed.
[0050] (4) Performance test: The battery was subjected to constant current charge and discharge test at a current density of 2 mA / g, with a test voltage range of 0 to 1.8 V, and a cycle stability test for 500 cycles.
[0051] Example 6: Preparation of α-MnO2 negative electrode material and battery assembly
[0052] (1) Preparation of negative electrode material: Using the same method as in Example 1, 80% α-MnO2 and 10% superconducting carbon black (Super P) were ground and stirred evenly, and then 10% polyvinylidene fluoride (PVDF) binder was added to grind into slurry. Then, N-methylpyrrolidone (NMP) was added to the mixture as a solvent to obtain a viscous slurry. The slurry was evenly coated on a graphite foil current collector with a coating thickness of 200 μm and dried at 60°C for 6 hours to remove the NMP solvent.
[0053] (2) Preparation of positive electrode materials: Commercially available LiCoO2 was used as the positive electrode material, mixed with 10% conductive carbon black and 10% PVDF, coated on aluminum foil, and subjected to the same drying process.
[0054] (3) Battery assembly: The positive electrode, separator and negative electrode are stacked in sequence and loaded into a CR2032 coin-type battery case. A 2M electrolyte solution with a molar ratio of water to additive dimethyl sulfoxide of 1:1 is injected. The electrolyte is lithium bis(trifluoromethylsulfonyl)imide (LiTFSI). Glass fiber is used as a separator. Finally, the battery case is sealed.
[0055] (4) Performance test: The battery was subjected to constant current charge and discharge test at a current density of 2 mA / g, with a test voltage range of 0 to 1.8 V, and a cycle stability test for 500 cycles.
[0056] Example 7: Preparation of α-MnO2 and γ-MnO2 mixed negative electrode material and battery assembly
[0057] (1) Preparation of negative electrode material: The material obtained by mixing α-MnO2 and γ-MnO2 powders in a ratio of 1:1 was ground and stirred evenly with 70% and 20% superconducting carbon black (Super P), and then 10% polyvinylidene fluoride (PVDF) binder was added to grind into slurry. Then, N-methylpyrrolidone (NMP) was added to the mixture as a solvent to obtain a viscous slurry. The slurry was evenly coated on the graphite foil current collector with a coating thickness of 200 μm and dried at 70°C for 8 hours to remove the NMP solvent.
[0058] (2) Preparation of positive electrode material: Commercially available LiFePO4 was used as the positive electrode material, mixed with 10% conductive carbon black and 10% PVDF, coated on aluminum foil, and subjected to the same drying process.
[0059] (3) Battery assembly: The positive electrode, separator and negative electrode are stacked in sequence and loaded into a CR2032 coin-type battery case. A 2M lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) aqueous solution is injected as the electrolyte. A polypropylene separator is used, and finally the battery case is sealed.
[0060] (4) Performance test: The battery was subjected to constant current charge and discharge test at a current density of 1.0 mA / g, with a test voltage range of 0 to 2.0 V, and a cycle stability test for 800 cycles.
Claims
1. An aqueous lithium-ion battery, characterized in that: The battery comprises: a battery housing and a positive electrode, a negative electrode, an aqueous electrolyte and a diaphragm placed in the battery housing; the active material of the positive electrode comprises LiCoO2, LiMn2O4, LiFePO4 or LiNi 0.5 Mn 1.5 O4; the active material of the negative electrode includes one or more materials selected from α-MnO2, γ-MnO2, and δ-MnO2.
2. An aqueous lithium-ion battery according to claim 1, characterized in that: The aqueous electrolyte includes a water-soluble lithium salt solution and an additive.
3. An aqueous lithium-ion battery according to claim 1, characterized in that: The diaphragm includes polyethylene diaphragm, polypropylene diaphragm, glass fiber diaphragm, non-woven fabric, Nafion membrane and composite membrane thereof.
4. An aqueous lithium-ion battery as claimed in claim 2, characterized in that: In the electrolyte, the molar concentration of lithium salt dissolved in the mixed solvent may be 0.05 to 20 mol / kg; and the molar mass ratio of water to additives is 0.1:2 to 3:
1.
5. A method for preparing an aqueous lithium-ion battery, characterized in that: For preparing an aqueous lithium-ion battery as claimed in any one of claims 1 to 4, the method comprises the following steps: A negative electrode slurry containing one or more materials of α-MnO2, γ-MnO2, and δ-MnO2 is coated on the surface of the negative electrode collector and dried by heating to form a negative electrode; the positive electrode, separator, and negative electrode are processed and formed into the battery casing, and an aqueous electrolyte is added into the battery casing and then sealed to obtain the aqueous lithium-ion battery.
6. The method for preparing an aqueous lithium-ion battery according to claim 2, characterized in that: The lithium salt is at least one of lithium perchlorate (LiCIO4), lithium nitrate (LiNO3), lithium sulfate (LiSO4), lithium hexafluorophosphate (LiPF6), lithium bis(oxalate borate) (LiB(C2O4)2), lithium difluorooxalatoborate (LiBF4) and lithium bis(trifluoromethylsulfonyl imide) (LiTFSI); 7. The method for preparing an aqueous lithium-ion battery according to claim 2, characterized in that: The additive is at least one of a carbonate compound, a sulfonyl compound and a cyano compound. The carbonate compounds include ethylene carbonate and fluoroethylene carbonate; the sulfonyl compounds include dimethyl sulfoxide, thionyl chloride, sulfuryl chloride and benzenesulfonyl chloride; the cyano compounds include acetonitrile, succinonitrile and glutaronitrile.
8. The method for preparing an aqueous lithium-ion battery according to claim 4, characterized in that: The said will contain LiCoO2, LiMn2O4, LiFePO4 or LiNi 0.5 Mn 1.5 The positive electrode prepared by coating LiCoO2, LiMn2O4, LiFePO4 or LiNi 0.5 Mn 1.5 The O4 material, conductive carbon black (Super P), and polyvinylidene fluoride (PVDF) are ground and mixed in a mass ratio of 6-9:0.2-4:0.2-4, and then N-methylpyrrolidone (NMP) is added and mixed to prepare the positive electrode slurry.
9. The method for preparing an aqueous lithium-ion battery according to claim 4, characterized in that: The positive electrode current collector includes copper foil, stainless steel foil, aluminum foil, titanium foil, graphite foil, nickel foil, carbon fiber cloth or a composite current collector, such as conductive resin, carbon-coated aluminum foil and titanium-nickel shape memory alloy.
10. The method for preparing an aqueous lithium-ion battery according to claim 4, characterized in that: The process of coating a negative electrode slurry containing one or more materials of α-MnO2, δ-MnO2, and γ-MnO2 on the surface of a negative electrode current collector to form a negative electrode comprises: grinding and mixing one or more materials of layered α-MnO2, δ-MnO2, and γ-MnO2 nanorods, conductive carbon black (Super P), and polyvinylidene fluoride (PVDF) in a mass ratio of 6-9:0.2-4:0.2-4, and then adding N-methylpyrrolidone (NMP) to mix to obtain the negative electrode slurry.